Integrating Ecopedagogy into the Islamic Religious Education Curriculum to Foster Ecological Awareness - Wati, Salmi; Eliwatis; Kuriaya, Kunalan; Akhyar, Muaddyl (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Environmental degradation and climate change pose serious global challenges that demand educational responses, including in religious education. This study examines the integration of ecological awareness into the Islamic Religious Education (PAI) curriculum through an ecopedagogical approach rooted in Islamic values. Utilizing a literature review method, the study reveals that the current PAI curriculum remains focused on theological aspects, ritual worship, and moral development, while the ecological dimension embodied in Islamic teachings such as the concepts of khalifah fil ard (humans as stewards of the Earth) and fiqh al-bi’ah (environmental ethics) has not been comprehensively accommodated. The analysis indicates a substantial gap between Islamic teachings emphasizing environmental preservation and their implementation at the educational level, resulting in low levels of ecological awareness and concern among students. As a constructive alternative, the development of a more integrative and transformative PAI curriculum incorporating ecopedagogical principles based on Islamic values is proposed. Through this approach, students are expected not only to be religious in a ritual sense but also to develop a high level of ecological consciousness and to internalize social and spiritual responsibilities in preserving the environment. The novelty of this study lies in the formulation of a PAI curriculum model grounded in ecopedagogy that integrates Islamic spirituality with environmental sustainability principles, thus offering practical contributions to character education enhancement and the development of ecological awareness among young Muslim generations. The research findings imply the need for policy reforms and curriculum redesign to ensure Islamic education actively contributes to shaping environmentally responsible future generations.